KOMUNITAS PEDESAAN DAN POLA SELEKTIFITAS INTERNET (Survai Komunitas Desa Kading, Kecamatan Tanete Riaja, Kabupaten Barru, Provinsi Sulawesi Selatan) - Rukman Pala (BPSDMP Kominfo Jakarta, 2015)
This study Background is to view the rural community condition regarding internet. This study focuses on the selectivity pattern issue of internet access and these pattern significance with rural communities characteristics. The findings of rural community activity phenomenon -in the context of audience orientation dimensions, at the level selectivity, involvement and utilization which- shows the the internet use variation, become evidence that individuals in rural communities are active. Activities theoretically occur because peoples in rural communities psychologically have